Homepage de fanfictions: um estudo bidimensional de gênero na concepção sociorretórica - Moraes, Elaine Valencise Hidalgo de (2009)
This study aims to analyse a website homepage which contains fanfictions - stories written by fans under the perspective of the socio-rhetorical analysis of textual genres. Specific objectives include: to understand the organisation of the admiring readers and writers of online fanfictions, checking how such groups might fall under the Swales (1990) concept of discourse communities, which he applies to academic communities; to outline a characterization of a fanfiction website and the existing involvement among its users; to discuss the situational context within which the digital fanfiction activities evolve; and to see if Askehave and Nielsen's (2004) bidimentional model of analysis of web files can be applied to the homepage of a fanfiction website. The corpus is the result of a research of ethnographic nature carried out on a specific fanfiction website: Fanfic Addiction. Focus falls primarily on the application of the Swales (1990) criteria of discourse communities to the website user group and on the application of Bhatia's (1993) methodology to the study of textual genres. Attention then shifts to the study of the website homepage using Askehave and Nielsen's (2004) model for digital genres. This study shows that readers and writers of Fanfic Addiction, according to Swales (1990) criteria, are a discourse community, even if they do not constitute an academic community. This study also yields other significant insights, namely the light shed on the context of production of fanfictions, the involvement between admiring readers and writers, and the historical aspects pertaining to such activity. With regards to the study of the fanfiction homepage, it was also observed the feasibility of applying to this genre of website the bidimentional model of analysis, in which the close relationship between the digital environment and textual genres is considered